Self-propelled Employees – Co-workership in Swedish Community Pharmacies - Hagsten, Kenneth; Eriksson, Andrea; Palm, Kristina (Nordic Journal of Working Life Studies, 2023)
In this article, work in Swedish pharmacies is examined.With the Nordic concept of co-workership as a frame, the aim is to examine how employees in pharmacies view and handle their work situations and the reasons behind them. Data were mainly collected with 20 qualitative semi-structured interviews in five different pharmacies. The data were organized and analyzed by using the content analysis process. In the studied pharmacies, it can be summarized as work was carengried out in a self-propelled way. Employees take an overall responsibility for the workplace, have ambition to help others and to be a part of a good team, while most of the work is carried out individually and independently.